2018
DOI: 10.1116/1.5013670
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and reproducible in-depth observation of organic–inorganic hybrid materials using FIB-TOF-SIMS

Abstract: In order to overcome the limitations of sputter depth profiling, the authors have introduced focused ion beam-time-of-flight secondary ion mass spectrometry (FIB-TOF-SIMS). In this article, the authors summarize our investigation into the capability of Ar-gas cluster ion beam (GCIB) to remove FIB-induced molecular damage. The analysis of organic-inorganic hybrid mixture samples is applied and discussed. The authors demonstrate a method whereby the accurate and reproducible chemical depth distributions of atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Added to Figure are similar measurements extracted from Figure of Iida et al's detailed study for the Ar + GCIB cleaning of flat Ga + implanted, PC at 48° incidence. These are shown as orange circles and are for cleaning using 20‐keV Ar 2500 + at 40° incidence.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Added to Figure are similar measurements extracted from Figure of Iida et al's detailed study for the Ar + GCIB cleaning of flat Ga + implanted, PC at 48° incidence. These are shown as orange circles and are for cleaning using 20‐keV Ar 2500 + at 40° incidence.…”
Section: Resultsmentioning
confidence: 92%
“…For this condition, the sputtering yield of pure PC is 60 nm 3 . Iida et al do not give the Ga + profiles but only the Ar + GCIB recovery dose as a function of the implanted Ga + dose. For our purposes, to determine the effective sputtering yield, we use the SRIM‐calculated Ga + implantation depth in PC and a fraction of 57% of the recovery dose to allow for the difference between their measure of the recovery dose and the centroid of the Ga + profile, assumed to be of a similar scaling to our data for PS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOF‐SIMS is a powerful analysis technique which allows us to directly observe molecular information. Furthermore, after the advent of the argon‐gas cluster ion beam (Ar‐GCIB), the combination of bismuth cluster and Ar‐GCIB has enabled determination of three‐dimensional molecular distributions with high spatial resolution . Presently, Bi/Ar‐GCIB dual‐beam depth profiling is a common and indispensable analysis technique for characterization of OLED devices .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after the advent of the argon-gas cluster ion beam (Ar-GCIB), 6,7 the combination of bismuth cluster and Ar-GCIB has enabled determination of three-dimensional molecular distributions with high spatial resolution. 8,9 Presently, Bi/Ar-GCIB dual-beam depth profiling is a common and indispensable analysis technique for characterization of OLED devices. 10 However, in general, an OLED has five to seven organic layers, and it is often observed that the fragment ions interfere with each other and confuse the interlayer boundaries because it cannot be known a priori from which molecule (s) the fragment ions arise.…”
Section: Introductionmentioning
confidence: 99%